An integrated approach for the mitigation of acid rock drainage (ARD) associated with pyrrhotite in nickel deposits - Chimbganda, Tapiwa (Centre for Bioprocess Engineering Research, 2015)
This project identified the possibility of manipulating rejection mechanisms in flotation to produce passivated pyrrhotite tailings. Passivation enables surface coating of the sulfide thus inhibiting attack by oxidising agents. Promotion of passivation of pyrrhotite during flotation to produce un-reactive tailings has not been explored to date. Polyethylene polyamines (DETA/TETA), which are already used as depressants in flotation, have been proved to be effective coating agents, significantly reducing the oxidation of pyrrhotite and pyrite in both abiotic and biotic systems. However, passivation by polyethylene polyamines (DETA and TETA) has only been explored on waste rock and pristine pyrrhotite. Furthermore, studies of the mechanism of oxidation of pyrrhotite have observed the formation of a hydrophilic ferric oxyhydroxide layer which enables depression of pyrrhotite during flotation. This layer has been reported in literature to inhibit the further oxidation of the pyrrhotite surface. Thus passivation can also take advantage of the formation of the ferric oxyhydroxide layer to inhibit further oxidation of the mineral.